Genetics and the last stand of the Sumatran rhinoceros Dicerorhinus sumatrensis - Goossens, Benoît; Salgado-Lynn, Milena; Rovie-Ryan, Jeffrine J.; Ahmad, Abdul H.; Payne, Junaidi; Zainuddin, Zainal Z.; Nathan, Senthilvel K. S. S.; Ambu, Laurentius N. (Cambridge University Press, 2013)
The Sumatran rhinoceros Dicerorhinus sumatrensis is on the brink of extinction. Although habitat loss and poaching were the reasons of the decline, today's reproductive isolation is the main threat to the survival of the species. Genetic studies have played an important role in identifying conservation priorities, including for rhinoceroses. However, for a species such as the Sumatran rhinoceros, where time is of the essence in preventing extinction, to what extent should genetic and geographical distances be taken into account in deciding the most urgently needed conservation interventions? We propose that the populations of Sumatra and Borneo be considered as a single management unit.